2005
DOI: 10.1590/s0021-75572005000200013
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e desenvolvimento a longo prazo do prematuro extremo

Abstract: Suggested citation: Rugolo LM. Growth and developmental outcomes of the extremely preterm infant. J Pediatr (Rio J). 2005;81(1 Suppl):S101-S110. AbstractObjetive: To provide information for pediatricians and neonatologists to create realistic outcome expectations and thus help plan their actions.Sources of data: Searches were made of the Cochrane Library, MEDLINE, and Lilacs databases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0
149

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(204 citation statements)
references
References 52 publications
1
54
0
149
Order By: Relevance
“…[3][4][5][6] Infants born prematurely present developmental abnormalities with greater frequency than those born at full term. [7][8][9] Preterms may suffer from failure to thrive in terms of both height and weight, from motor development disorders, mental deficiencies, hearing loss, impaired vision, language difficulties, cardiovascular problems, respiratory problems, attention deficits and hyperactivity, among other problems. 3,10 The protocol used for follow-up of patients who have spent time in neonatal intensive care units includes a motor development evaluation and countless tools have been used to help professionals working in the area make more precise functional assessments.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Infants born prematurely present developmental abnormalities with greater frequency than those born at full term. [7][8][9] Preterms may suffer from failure to thrive in terms of both height and weight, from motor development disorders, mental deficiencies, hearing loss, impaired vision, language difficulties, cardiovascular problems, respiratory problems, attention deficits and hyperactivity, among other problems. 3,10 The protocol used for follow-up of patients who have spent time in neonatal intensive care units includes a motor development evaluation and countless tools have been used to help professionals working in the area make more precise functional assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Os avanços na área da Neonatologia tem promovido um aumento na sobrevivência de recém-nascidos com idade gestacional e peso de nascimento menores (Rugolo, 2005). Entretanto, os bebês que nascem prematuros (PT) (antes de 37 semanas de gestação) e com baixo peso (BP) (<2.500g) são mais vulneráveis a doenças e complicações, como enfermidades crônicas (broncodisplasia, síndrome do estresse respiratório, hemorragia intraventricular, retinopatia ou anemia da prematuridade, problemas cardiovasculares, dentre outros) e hospitalizações repetidas e/ou prolongadas (Bordin, Linhares & Jorge, 2001;Klebanov & Brooks-Gunn, 2006;Linhares, Chimello, Bordin, Carvalho & Martinez, 2005).…”
unclassified
“…Some authors advocate its use (15,16), while others believe that age correction may overstate preterm performance in comparison to those born full term at two years of age (30). D' Agostino et al (31) reported that despite the international recommendation for age adjustment in premature infants, most professionals working in primary care do not use it, and that this fact has important implications for the care, such as erroneous detection of delays and early prescriptions.…”
Section: Discussionmentioning
confidence: 99%